Truth as Gift and Vocation: New Perspectives on Revelation. (November 2019) - Fortin, Jean-Pierre
This article proposes to draw significant anthropological implications of a personally focused and historically contextualized understanding of revelation. Building on the work of Christoph Theobald, it uses Karl Rahner's and Dietrich Bonhoeffer's theology of discipleship to retrieve and expand Dei Verbum 's understanding of human history as revelation. Revelation is both gift and vocation. The gift that is revelation defines for those who receive it a new vocation: to bear witness to the truth in their person, words, and deeds. This understanding is then put to the test of mystical experience by means of the analysis of Julian of Norwich's Showings . Mystical encounter with the crucified Lord indeed compelled the 14th-century mystic to undertake the lifelong interpretation of the truth received, which itself led her to become a powerful witness, theologian, and spiritual guide.